Adhesive and preparation method thereof, positive plate and battery

By introducing functional groups into the binder and optimizing the proportion of copolymerization units, the alkali resistance problem of the binder in the highly alkaline system is solved, and the circulation performance of the battery and the stability of the slurry processing are improved.

CN119505761APending Publication Date: 2025-02-25SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411657359.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the binder has a problem of poor alkali resistance in the positive electrode slurry, especially in highly alkaline systems, which is prone to gel phenomenon, which affects the capacity maintenance and service life of the battery.

Method used

A new binder is provided, which contains no fluorine on its branch chain, and enhances alkali resistance and stability of the binder by introducing specific functionalized groups and optimizing the proportion of copolymerized units.

Benefits of technology

This binder can remain stable in a highly alkaline environment, avoid chain reactions and defluorination, and improve the circulation performance of the battery and the stability of slurry processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505761A_ABST
    Figure CN119505761A_ABST
Patent Text Reader

Abstract

The invention provides an adhesive and a preparation method thereof, a positive plate and a battery. The structure of the adhesive is # imgabs0 #; wherein i is any integer from 5 to 10, j is any integer from 1 to 5, k is any integer from 5 to 10, and l is any integer from 1 to 5; n is any integer from 2 to 15; r1 is selected from any one of substituted or non-substituted C1-C10 alkyl, substituted or non-substituted C1-C10 alkoxy and-NH2, R2 is selected from any one of-OH,-NH2,-B (OH) 2,-CN,-SO3M,-PO3HM,-PO3M2 and-COOM, and M is selected from any one of H < + >, Li < + >, Na < + >, K < + > and NH4 < + >. The binder provided by the invention not only solves the alkali resistance problem of traditional PVDF in a high-alkalinity system, but also improves the cycle performance of a battery cell and the stability of slurry processing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an adhesive and a preparation method thereof, a positive electrode sheet and a battery. Background Art

[0002] PVDF (polyvinylidene fluoride) binder can bond active materials (such as lithium iron phosphate, ternary positive electrode materials and sodium positive electrode materials, etc.), conductive agents and current collectors on the positive electrode of the battery, maintain the uniformity and stability of the active material during slurrying, provide the required electronic conduction in the electrode, and play a vital role in maintaining the capacity, service life, and stability of the battery. However, the homopolymer PVDF has poor adhesion, poor alkali resistance in ternary positive electrode slurry and sodium positive electrode, and is prone to gel problems. In order to improve the adhesion of PVDF and its alkali resistance in the high alkaline system of power batteries, polar comonomers are usually introduced into PVDF, such as acrylic acid, maleic anhydride ester monomers, etc. The polar comonomers used in copolymer-modified PVDF contain carboxyl groups, which can have good adhesion in the ternary system of power batteries. However, in the ternary positive electrode with higher alkalinity (nickel content exceeds 90%) or sodium battery positive electrode system, even if the content of carboxyl copolymer is further increased, the copolymer-modified PVDF still has gelation phenomenon and poor alkali resistance. Although the above modification methods can play a certain role, they cannot completely eliminate the risk. Summary of the invention

[0003] The main purpose of the present invention is to provide a binder and a preparation method thereof, a positive electrode sheet and a battery, so as to solve the problem of poor alkali resistance of the binder in the positive electrode slurry in the prior art.

[0004] In order to achieve the above object, according to one aspect of the present invention, a bonding agent is provided, the structure of which is as follows:

[0005]

[0006] wherein i is any integer from 5 to 10, j is any integer from 1 to 5, k is any integer from 5 to 10, l is any integer from 1 to 5; n is any integer from 2 to 15; R1 is selected from substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C1~C 10 any one of -OH, -NH2, -B(OH)2, -CN, -SO3M, -PO3HM, -PO3M2 and -COOM, wherein M is selected from H + , Li + 、Na + , K + and NH4+ Any one of .

[0007] Furthermore, the ratio of the above i, j, k and l is 8-10:3-5:7-10:1-3.

[0008] Furthermore, the above n is any integer from 5 to 10.

[0009] Further, the above R1 is selected from any one of substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C1-C5 alkoxy and -NH2; preferably R1 is methyl and / or ethyl; and / or R2 is -SO3M, wherein M is selected from H + , Li + 、Na + , K + and NH 4+ Any one of, preferably R2 is a potassium sulfonate group; more preferably, the structure of the binder is

[0010]

[0011] Furthermore, the weight average molecular weight of the above-mentioned binder is 7×10 5 ~11×10 5 g / mol.

[0012] According to another aspect of the present invention, a method for preparing the aforementioned adhesive is provided, the method comprising: and an initiator raw material are mixed and then polymerized to obtain a binder; wherein, The molar ratio is i:j:k:l, and i, j, k and l are the same as i, j, k and l in the above description; R1, R2 and n are the same as R1, R2 and n in the above description.

[0013] Furthermore, the polymerization reaction temperature is 60-70° C.; and / or the polymerization reaction time is 15-19 hours.

[0014] Furthermore, the mass proportion of the initiator in the above raw materials is 2-5%; preferably, the initiator is azobisisobutyronitrile and / or dibenzoyl peroxide.

[0015] According to another aspect of the present invention, there is provided a positive electrode sheet, comprising a positive electrode active material, a conductive agent and a binder, wherein the binder is the aforementioned binder.

[0016] According to another aspect of the present invention, a battery is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, wherein the positive electrode sheet is the positive electrode sheet mentioned above.

[0017] By applying the technical solution of the present application, the side chains of the adhesive of the present application do not contain fluorine, and the phenomenon that a chain reaction occurs in a strong alkaline environment like PVDF, defluorination forms HF, and thus causes the adhesive to fail will not occur. The adhesive of the present application fundamentally eliminates this chain reaction, so the adhesive of the present application can have better alkali resistance. On the one hand, the presence of the R2 group in the adhesive helps to promote the formation of the SEI film, thereby helping to reduce the side reactions of the active substances during the cycle process, and then help to improve the cycle performance and capacity retention rate of the battery cell; on the other hand, the R2 group can form a stronger bond with the positive ions in the alkaline environment, enhance the stability of the adhesive under alkaline conditions, prevent its structure from being destroyed when the battery is working, and maintain good bonding performance. The presence of other side chains in the adhesive helps to improve the contact between the electrolyte and the electrode, promote ion transmission, and then help to improve the electrochemical performance of the battery, especially the cycle stability during high current charging and discharging. By adjusting the ratio of the R1 group, the R2 group and the copolymer unit, the viscosity of the slurry can be controlled, which helps to avoid stratification, gelation and other problems during long-term standing or processing, thereby helping to improve the uniformity and stability of the slurry during the coating process. The optimized copolymer unit ratio and functionalized groups help the slurry to maintain good fluidity and stability even at high solid content, which is beneficial to improve processing efficiency and the quality of the electrode sheet, and reduce the process processing risks caused by viscosity changes. Therefore, the binder of the present application not only solves the alkali resistance problem of traditional PVDF in high alkaline systems by introducing specific functionalized groups and optimizing the copolymer unit ratio, but also improves the cycle performance of battery cells and the stability of slurry processing. DETAILED DESCRIPTION

[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0019] As analyzed in the background technology of this application, the binder in the prior art has the problem of poor alkali resistance in the positive electrode slurry. In order to solve this problem, this application provides a binder and a preparation method thereof, a positive electrode sheet and a battery.

[0020] In a typical embodiment of the present application, an adhesive is provided, the structure of the adhesive is

[0021]

[0022] wherein i is any integer from 5 to 10, j is any integer from 1 to 5, k is any integer from 5 to 10, l is any integer from 1 to 5; n is any integer from 2 to 15; R1 is selected from substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C1~C 10any one of -OH, -NH2, -B(OH)2, -CN, -SO3M, -PO3HM, -PO3M2 and -COOM, wherein M is selected from H + , Li + 、Na + , K + and NH 4+ Any one of .

[0023] The side chains of the binder of the present application do not contain fluorine, and there will be no chain reaction like PVDF in a strong alkaline environment, defluorination to form HF, which will cause the binder to fail. The binder of the present application fundamentally eliminates this chain reaction, so the binder of the present application can have better alkali resistance. On the one hand, the presence of the R2 group in the binder helps to promote the formation of the SEI film, thereby helping to reduce the side reactions of the active substances during the cycle process, and then help to improve the cycle performance and capacity retention rate of the battery cell; on the other hand, the R2 group can form a stronger bond with the positive ions in the alkaline environment, enhance the stability of the binder under alkaline conditions, prevent its structure from being destroyed when the battery is working, and maintain good bonding performance. The presence of other side chains in the binder helps to improve the contact between the electrolyte and the electrode, promote ion transfer, and then help to improve the electrochemical performance of the battery, especially the cycle stability during high current charging and discharging. By adjusting the ratio of the R1 group, the R2 group and the copolymer unit, the viscosity of the slurry can be controlled, which helps to avoid stratification, gelation and other problems during long-term standing or processing, thereby helping to improve the uniformity and stability of the slurry during the coating process. The optimized copolymer unit ratio and functionalized groups help the slurry to maintain good fluidity and stability even at high solid content, which is beneficial to improve processing efficiency and the quality of the electrode sheet, and reduce the process processing risks caused by viscosity changes. Therefore, the binder of the present application not only solves the alkali resistance problem of traditional PVDF in high alkaline systems by introducing specific functionalized groups and optimizing the copolymer unit ratio, but also improves the cycle performance of battery cells and the stability of slurry processing.

[0024] In order to further improve the cycle performance of the battery cell and the stability of the slurry processing, in one embodiment of the present application, the ratio of i, j, k and l is preferably 8-10:3-5:7-10:1-3.

[0025] In one embodiment of the present application, the above n is any integer between 5 and 10.

[0026] The polyethylene glycol side chain group can not only improve the processing performance of the battery slurry, but also optimize the interface characteristics between the electrode layer and the electrolyte. It is preferred to control n in the polyethylene glycol side chain group within the above range, which helps to further improve the fluidity and uniformity of the slurry, improve the compatibility between the binder and the electrolyte, and help form a stable SEI film, thereby helping to reduce the decomposition of the electrolyte and improve the cycle stability and safety of the battery.

[0027] In order to further improve the stability of the slurry, in one embodiment of the present application, it is preferred that the above R1 is selected from any one of substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C1-C5 alkoxy and -NH2; preferably R1 is methyl and / or ethyl; and / or R2 is -SO3M, wherein M is selected from H + , Li + 、Na + , K + and NH 4+ Any one of, preferably R2 is a potassium sulfonate group; more preferably, the structure of the binder is

[0028]

[0029] In one embodiment of the present application, the weight average molecular weight of the binder is 7×10 5 ~11×10 5 g / mol.

[0030] If the weight average molecular weight of the binder is too low, it may cause uneven distribution of the binder in the electrode, affecting the uniformity and overall performance of the electrode; if the weight average molecular weight of the binder is too high, the binder may be too viscous, affecting the processing performance of the slurry and increasing the difficulty of manufacturing the electrode sheet. It is preferred to control the weight average molecular weight of the binder within the above range, which helps to balance the physical and chemical properties of the binder, so as to achieve the purpose of improving the electrochemical performance, processing adaptability and structural stability of the battery.

[0031] In another typical embodiment of the present application, a method for preparing the aforementioned adhesive is provided, the method comprising: and an initiator raw material are mixed and then polymerized to obtain a binder; wherein, The molar ratio is i:j:k:l, and i, j, k and l are the same as i, j, k and l in the above description; R1, R2 and n are the same as R1, R2 and n in the above description.

[0032] The polymerization reaction of the present application is a polymerization between carbon-carbon double bonds, and a binder having a carbon chain as the main chain and a functional group on the side chain is formed by the polymerization reaction. Preferably, the molar ratio between each monomer is within the above range, which helps to adjust the ratio of the R1 group and the R2 group and the copolymerization unit, and control the viscosity of the slurry, thereby helping to avoid problems such as stratification and gelation during long-term standing or processing, and then helping to improve the uniformity and stability of the slurry during the coating process. The optimized copolymerization unit ratio and functionalized group help to keep the slurry in good fluidity and stability even at a high solid content, which is beneficial to improve the processing efficiency and the quality of the electrode sheet, and reduce the process processing risk caused by viscosity changes.

[0033] In order to control the weight average molecular weight of the binder within an appropriate range, thereby improving the cycle performance of the battery cell and the stability of the slurry processing, in one embodiment of the present application, the polymerization reaction temperature is preferably 60 to 70°C; and / or the polymerization reaction time is 15 to 19 hours.

[0034] In order to improve the efficiency of the polymerization reaction, in one embodiment of the present application, the mass proportion of the initiator in the above raw materials is preferably 2-5%; the preferred initiator is azobisisobutyronitrile and / or dibenzoyl peroxide.

[0035] In another typical embodiment of the present application, a positive electrode sheet is provided, comprising a positive electrode active material, a conductive agent and a binder, wherein the binder is the aforementioned binder.

[0036] Since the positive electrode sheet contains the binder of the present application, the positive electrode sheet has higher cycle stability.

[0037] In another typical embodiment of the present application, a battery is provided, including a positive electrode sheet, an electrolyte and a negative electrode sheet, and the positive electrode sheet is the positive electrode sheet mentioned above.

[0038] Since the positive electrode sheet of the above-mentioned battery contains the binder of the present application, the battery has higher cycle stability.

[0039] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0040] Example 1

[0041] Monomer 1, monomer 2, monomer 3, monomer 4 and initiator dibenzoyl peroxide (BPO) were mixed into a mixture and then subjected to polymerization reaction. The polymerization reaction temperature was 70° C., the polymerization reaction time was 17 h, the molar ratio of monomer 1, monomer 2, monomer 3 and monomer 4 was 10:5:7:3, the mass proportion of the initiator in the mixture was 3%, monomer 1 was methyl methacrylate, monomer 2 was poly(ethylene glycol) methacrylate, the polymerization degree was 5, and monomer 3 was Monomer 4 is 3-sulfonic acid propyl methacrylate potassium salt, and a binder is obtained, and the structural formula of the binder is

[0042]

[0043] , where i=10, j=5, k=7, l=3, n=5, and the weight average molecular weight of the binder is 8.2×10 5 g / mol.

[0044] Example 2

[0045] The difference from Example 1 is that the molar ratio of monomer 1, monomer 2, monomer 3, and monomer 4 is 8:3:10:1, and the final binder is obtained, and the structural formula of the binder is

[0046]

[0047] , where i=8, j=3, k=10, l=1, n=5, and the weight average molecular weight of the binder is 8.6×10 5 g / mol.

[0048] Example 3

[0049] The difference from Example 1 is that the molar ratio of monomer 1, monomer 2, monomer 3, and monomer 4 is 10:5:10:1, and the final binder is obtained, and the structural formula of the binder is

[0050]

[0051] , where i=10, j=5, k=10, l=1, n=5, and the weight average molecular weight of the binder is 9.1×10 5 g / mol.

[0052] Example 4

[0053] The difference from Example 1 is that the molar ratio of monomer 1, monomer 2, monomer 3, and monomer 4 is 5:1:5:5, and the final binder is obtained, and the structural formula of the binder is

[0054]

[0055] , where i=5, j=1, k=5, l=5, n=5, and the weight average molecular weight of the binder is 7.7×10 5 g / mol.

[0056] Example 5

[0057] The difference from Example 1 is that the degree of polymerization of poly(ethylene glycol) methacrylate is 10, and the final adhesive is the structural formula of the adhesive.

[0058]

[0059] , where i=10, j=5, k=7, l=3, n=10, and the weight average molecular weight of the binder is 8.5×10 5 g / mol.

[0060] Example 6

[0061] The difference from Example 1 is that the degree of polymerization of poly(ethylene glycol) methacrylate is 2, and the adhesive is finally obtained. The structural formula of the adhesive is

[0062]

[0063] , where i=10, j=5, k=7, l=3, n=2, and the weight average molecular weight of the binder is 7.1×10 5 g / mol.

[0064] Example 7

[0065] The difference from Example 1 is that the degree of polymerization of poly(ethylene glycol) methacrylate is 15, and the adhesive is finally obtained. The structural formula of the adhesive is

[0066]

[0067] , where i=10, j=5, k=7, l=3, n=15, and the weight average molecular weight of the binder is 7.0×10 5 g / mol.

[0068] Example 8

[0069] The difference from Example 1 is that monomer 1 is ethyl methacrylate, and the final binder is a binder having the structural formula:

[0070]

[0071] , where i=10, j=5, k=7, l=3, n=5, and the weight average molecular weight of the binder is 9.0×10 5 g / mol.

[0072] Example 9

[0073] The difference from Example 1 is that the polymerization temperature is 60°C, the polymerization time is 15h, the mass proportion of the initiator in the mixture is 2%, and the binder is finally obtained, and the weight average molecular weight of the binder is 7.2×10 5 g / mol.

[0074] Example 10

[0075] The difference from Example 1 is that the polymerization temperature is 70°C, the polymerization time is 19h, the mass proportion of the initiator in the mixture is 5%, and the binder is finally obtained, and the weight average molecular weight of the binder is 1×10 6 g / mol.

[0076] Embodiment 11

[0077] The difference from Example 1 is that the polymerization temperature is 40°C, the polymerization time is 10 h, the mass proportion of the initiator in the mixture is 1%, and the binder is finally obtained, and the weight average molecular weight of the binder is 3.0×10 5 g / mol.

[0078] Comparative Example 1

[0079] The adhesive is PVDF adhesive, HSV1810 purchased from Arkema.

[0080] Comparative Example 2

[0081] The difference from Example 1 is that the molar ratio of monomer 1, monomer 2, monomer 3, and monomer 4 is 4:7:3:6, and the final binder is obtained, and the structural formula of the binder is

[0082]

[0083] , where i=4, j=7, k=3, l=6, n=5, and the weight average molecular weight of the binder is 5.0×10 5 g / mol.

[0084] The binder prepared in the embodiment and the comparative example was used to prepare the slurry. NCM93, conductive agent and binder were dispersed in appropriate NMP at a mass ratio of 98:0.8:1.2, and the solid content was maintained at 70%. The mixture was stirred for 12 hours to obtain the slurry. The slurry was divided into two parts. One part of the slurry was evenly coated on aluminum foil and dried at 90°C for 12 hours under vacuum conditions to obtain a positive electrode sheet. The surface density of the obtained electrode sheet was 140g / m on a single side. 2 , compacted to 3.5g / cm 3 After drying, the electrode pieces were cut and transferred to the glove box. The lithium sheet was used as the counter electrode to assemble into a 2032 button cell. The electrolyte was a PC / EC (volume ratio 1:1) solution with 1M LiPF6 as the electrolyte, containing 3% FEC additive. The button cell was subjected to constant current charge and discharge test, and charged and discharged at room temperature with a current of 1C. The results are shown in Table 1. Another part of the slurry was used to stand for 24h and 48h to observe the stratification, viscosity and solid content of the slurry. The results are shown in Table 2.

[0085] Table 1

[0086]

[0087]

[0088] Table 2

[0089]

[0090] It can be seen from Table 1 and Table 2 that in Examples 1 to 3, Monomer 1, Monomer 2, Monomer 3, and Monomer 4 are in suitable proportions. Compared with Example 4, the slurry is left standing for 24 hours without stratification, the solid content is normal, and the battery has higher cycle stability; in Examples 5 and 6, the degree of polymerization of poly(ethylene glycol) methacrylate is within a suitable range. Compared with Example 7, the slurry has higher stability and the battery has higher cycle stability; in Examples 9 and 10, the polymerization reaction is carried out at a suitable temperature and time to form a binder with a suitable weight average molecular weight. Compared with Example 11, the slurry is left standing for 48 hours without stratification, and there is no difference in the solid content of the upper and lower layers.

[0091] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0092] The side chains of the binder of the present application do not contain fluorine, and there will be no chain reaction like PVDF in a strong alkaline environment, defluorination to form HF, which will cause the binder to fail. The binder of the present application fundamentally eliminates this chain reaction, so the binder of the present application can have better alkali resistance. On the one hand, the presence of the R2 group in the binder helps to promote the formation of the SEI film, thereby helping to reduce the side reactions of the active substances during the cycle process, and then help to improve the cycle performance and capacity retention rate of the battery cell; on the other hand, the R2 group can form a stronger bond with the positive ions in the alkaline environment, enhance the stability of the binder under alkaline conditions, prevent its structure from being destroyed when the battery is working, and maintain good bonding performance. The presence of other side chains in the binder helps to improve the contact between the electrolyte and the electrode, promote ion transfer, and then help to improve the electrochemical performance of the battery, especially the cycle stability during high current charging and discharging. By adjusting the ratio of the R1 group, the R2 group and the copolymer unit, the viscosity of the slurry can be controlled, which helps to avoid stratification, gelation and other problems during long-term standing or processing, thereby helping to improve the uniformity and stability of the slurry during the coating process. The optimized copolymer unit ratio and functionalized groups help the slurry to maintain good fluidity and stability even at high solid content, which is beneficial to improve processing efficiency and the quality of the electrode sheet, and reduce the process processing risks caused by viscosity changes. Therefore, the binder of the present application not only solves the alkali resistance problem of traditional PVDF in high alkaline systems by introducing specific functionalized groups and optimizing the copolymer unit ratio, but also improves the cycle performance of battery cells and the stability of slurry processing.

[0093] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An adhesive, characterized in that: The structure of the adhesive is ; wherein i is any integer from 5 to 10, j is any integer from 1 to 5, k is any integer from 5 to 10, l is any integer from 1 to 5; n is any integer from 2 to 15; R1 is selected from substituted or unsubstituted C1 to C 10 Alkyl, substituted or unsubstituted C1~C 10 Any one of -NH2, -OH, -NH2, -B(OH)2, -CN, -SO3M, Any one of -PO3HM, -PO3M2 and -COOM, wherein M is selected from H + , Li + 、Na + , K + and NH 4+ Any one of .

2. The adhesive according to claim 1, characterized in that: The ratio of the i, j, k and l is 8-10:3-5:7-10:1-3.

3. The adhesive according to claim 1 or 2, characterized in that: The n is any integer from 5 to 10.

4. The adhesive according to any one of claims 1 to 3, characterized in that: The R1 is selected from any one of substituted or unsubstituted C1-C5 alkyl, substituted or unsubstituted C1-C5 alkoxy and -NH2; preferably, the R1 is methyl and / or ethyl; And / or, said R2 is -SO3M, wherein M is selected from H + , Li + 、Na + , K + and NH 4+ Any one of the above, preferably, R2 is a potassium sulfonate group; More preferably, the structure of the adhesive is or 5. The adhesive according to any one of claims 1 to 4, characterized in that: The weight average molecular weight of the binder is 7×10 5 ~11×10 5 g / mol.

6. A method for preparing the adhesive according to any one of claims 1 to 5, characterized in that: The preparation method comprises: Will include and an initiator are mixed and polymerized to obtain a binder; wherein the Said Said and stated The molar ratio is i:j:k:l, and the i, the j, the k and the l are the same as the i, j, k and l described in claim 1; R1, R2 and n are the same as the R1, R2 and n described in claim 1.

7. The preparation method according to claim 6, characterized in that: The polymerization reaction temperature is 60-70° C.; and / or the polymerization reaction time is 15-19 hours.

8. The preparation method according to claim 6 or 7, characterized in that: The mass proportion of the initiator in the raw materials is 2-5%; preferably, the initiator is azobisisobutyronitrile and / or dibenzoyl peroxide.

9. A positive electrode sheet, comprising a positive electrode active material, a conductive agent and a binder, characterized in that: The adhesive is the adhesive according to any one of claims 1 to 5.

10. A battery comprising a positive electrode sheet, an electrolyte and a negative electrode sheet, characterized in that: The positive electrode sheet is the positive electrode sheet according to claim 9.